Comparison of Pb, Zn, Cd, As, Cr, Mo and Sb adsorption onto natural surface coatings in a stream draining natural as geochemical anomaly - Drahota, Petr; Skaloud, Pavel; Nováková, Barbara; Mihaljevič, Martin (Bulletin of environmental contamination and toxicology, 2014)
Natural surface coatings (biofilms) were collected on glass slides in the shallow, arsenic-rich stream and were used to compare biofilm trace element adsorption properties. Biofilm element retention and affinities were element specific indicating different processes control their sequestration. Distribution coefficients (K d values), calculated as the ratio between biofilm and dissolved trace element concentrations, revealed solid phase enrichment that, depending on the trace element, extended from 10(0.18) to 10(3.17). Elements were specifically scavenged by the organic constituents of the biofilm itself (Fe, Pb, Zn, Cr) and associated biominerals of poorly ordered Mn oxide (Cd, As, Mo, Sb). The results provide an evidence for the significant role that microbial activity can play in trace element geochemistry in freshwater environment.
Keywords: Trace Elements; Rivers; oxidy; Metals, Heavy; arsen; řeky; Arsenic; Adsorption; těžké kovy; stopové prvky; adsorpce; Oxides; biofilmy; organické látky; Organic Chemicals; Biofilms